Generalised trade‐off model for energy‐efficient WSN synchronisation. Issue 3 (1st February 2015) - Briff, P.; Lutenberg, A.; Rey Vega, L.; Vargas, F.; Patwary, M.
Abstract : A mathematical framework to obtain a generalised energy‐efficient trade‐off model for generic wireless sensor networks (WSNs) while attaining sensing node synchronisation at a given network‐wide estimation error threshold is presented. The model outputs both a theoretical optimal solution as well as a set of sub‐optimal solutions to cater for real‐world WSN designs. The robustness of the proposed framework is examined with an example in which randomly deployed sensors are affected by path‐loss and uncorrelated Rayleigh fading effects.